Calculating restaurant failure rates using longitudinal census data. Issue 4 (4th July 2019) - Healy, J. J.; Mac Con Iomaire, Máírtín
ABSTRACT: Failure rates in the restaurant industry are popularly perceived to be far higher than they actually are. This paper calculates failure rates in the Irish Food and Drinks Sector (IFDS), for the first time, using longitudinal census data from the Central Statistics Office (CSO) in Ireland, which follows the European statistical classification of economic activity (NACE). The results are compared with previously published literature on restaurant failure rates in the United States of America. This study also compares IFDS failure rates with other industry sectors in Ireland (construction, manufacturing). Drawing on Stinchcombe's 'liability of newness' theory, the informal fallacies theory 'Argumentum ad Populum', and critical success factors (CSFs) for restaurants theory, the paper explores restaurant failure rates both in Ireland and internationally. The research finds that the average failure rates for the IFDS are 15% after one year; 37.62% after three years; and 53.06% after five years in business, which, although marginally higher than other industry sectors in Ireland, are considerably lower than popularly perceived. Comparisons with previous studies in the United States of America shows that Irish rates are significantly lower, particularly in the first few years. The methodology can be replicated to provide comparative studies between other European countries using the NACE classifications. The results may assist in ensuring that future policy decisions made by governments, financial institutions and other restaurant/ hospitality industry groups are more empirically based and better informed.